(untitled) (Research, Society and Development, 2020)
Microorganism control in food has been a challenge due to the legislation restrictions of each country and the increase in the demand for food without chemical preservatives. Plant essential oils have antimicrobial action and are promising for the use in the food industry. Our study aimed to evaluate the chemical composition and the antimicrobial effect of Schinus terebinthifolius Raddi fruit essential oil on minas frescal cheese. The essential oil was extracted by hydrodistillation, and the chemical compounds were identified by gas chromatography coupled to mass spectrometry. The major identified compounds were hydrocarbon monoterpenes (57.0%), mainly: α-pinene (22.2%), limonene (17.0%), carvone (10.2%) and β-phellandrene (7.9%). The cheese was produced, the main microorganisms were isolated, and the minimum inhibitory concentration was determined through broth microdilution test. The cheese samples were soaked. The pink pepper fruit essential oil was added to the cheese samples at the concentration of 20000 μL/mL superficially or to the micelle. S. terebinthifolius fruit essential oil was efficient to control minas frescal cheese microorganisms mainly when applied by superficial addition. The essential oil is a potential source of studies to develop applications for the control of microorganisms in cheese such as minas frescal. Further studies may exploit the impact of the essential oil in minas frescal cheese acceptability.